2020
DOI: 10.1128/aac.02178-19
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Amikacin Administered Once Daily in Patients with Different Renal Functions

Abstract: The aim of this work was to evaluate the pharmacokinetics of amikacin in Mexican patients with different renal functions receiving once-daily dosing regimens and the influence of clinical and demographical covariates that may influence the optimization of this antibiotic. A prospective study was performed in a total of 63 patients with at least one determination of amikacin plasma concentration. Population pharmacokinetic (PK) parameters were estimated by nonlinear mixed-effects modeling; validations were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…Natural products such as Penicillin, Erythromycin, Cephalosporin C and Kanamycin are often used as main compounds in drug discoveries due to their potent bioactivity. Corresponding semi-synthesised derivatives Amoxicillin, Azithromycin, Cefpirome and Amikacin all exhibit higher potency than natural products [5][6][7] . Pleuromutilin (Figure 1, 1), a diterpenoid natural product from the basidiomycete species, shows moderate activities against Gram-positive strains and mycoplasmas 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Natural products such as Penicillin, Erythromycin, Cephalosporin C and Kanamycin are often used as main compounds in drug discoveries due to their potent bioactivity. Corresponding semi-synthesised derivatives Amoxicillin, Azithromycin, Cefpirome and Amikacin all exhibit higher potency than natural products [5][6][7] . Pleuromutilin (Figure 1, 1), a diterpenoid natural product from the basidiomycete species, shows moderate activities against Gram-positive strains and mycoplasmas 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Aminoglycosides are concentration-dependent agents and require a C max /MIC of 10 [ 61 ]. Two population pharmacokinetic studies focusing on amikacin concluded that ARC patients likely require increased dosing regimens [ 62 , 63 ]. Another pharmacokinetic modeling study in pediatric ICU patients who were administered tobramycin or gentamicin observed significantly lower median 24-h AUC (45.27 vs. 56.95 mg*h/L, p < 0.01) [ 64 ].…”
Section: Effects On Antibiotic Therapymentioning
confidence: 99%
“…After assessing the articles for eligibility by applying the inclusion and exclusion criteria, 19 publications were selected. In total, 6, 11, and 5 PopPK models were analyzed for amikacin [16][17][18][19][20][21], gentamicin [21][22][23][24][25][26][27][28][29][30][31] and tobramycin [32][33][34], respectively (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…All 19 studies included in this review used nonlinear mixed effect methods to analyze their data and develop PopPK models. As per Table 2 , a version of NONMEM software was used for the modeling in more than half of the studies (n=10) [19,[22][23][24][25][26][27][32][33][34]. Other software used were NPAG a function from the software Pmetrics (n=2) and the NPEM software (n=2).…”
Section: Population Pharmacokinetic Analysismentioning
confidence: 99%